The syntactical structure of Malay and Arabic: contrastive study - Ali, Asem Shehadeh Saleh; Hassan, Fekri Abidin (Center for Promoting Ideas (CPI), USA, 2011)
This paper is tries to contrast the syntactic structures between Arabic and Malay. The paper starts with introduction about contrastive study, then descriptive study for some aspects related to syntax of Malay and Arabic, as word-order, noun phrase, passive voice, object, and sentence, then followed by syntax of Arabic as well. Arabic structures were studied, the subject of nominal sentence and verbal sentence are described as well as Malay. The study contrasts between both languages by comparing the subject in syntax, and found out some similarities in nominal sentences, conditional sentences and specified the differences in subject NP immediately dominated by the node S is the subject.